Books from Ireland, Fifth to Ninth Centuries - Sharpe, Richard (Peritia, 2010)
Abstract The first part is concerned with extant books produced in Ireland and surviving elsewhere, the second with texts composed there but transmitted through copies made elsewhere, which alone survive. I also investigate text-historical evidence that allows one to trace copies of Late Antique texts from Ireland into seventh-century Northumbria, further evidence of the export of books from Ireland. The external survival of books made in Ireland, of texts composed in Ireland but not preserved there, and of texts read in Ireland and exported provides a counterweight to any positivist argument from the paucity of early medieval books made and preserved in Ireland that Irish book-culture was not as advanced as Bede’s or Aldhelm’s references would suggest. A similar case may be derived from vernacular texts. The only early manuscripts containing substantial quantities of Old Irish have survived on the Continent, but a large body of Old Irish texts has survived in Ireland, though few extant copies are anywhere near as old as the texts. Early Irish book-culture is therefore attested both through early manuscripts not in Ireland and through early texts not surviving in early Irish copies. The early medieval manuscripts preserved in Ireland, such as the gospel books of Durrow and Kells, have survived because of their special status as relics. Comparison with the evidence of manuscripts and texts from Africa and Spain in the early middle ages puts the Irish material into perspective.